Bahasa Sunda Di Jatinegara Kaum Dan Pemukiman Keturunan Pangeran Achmad Djaketra - Wati Kurniawati (Berkala Arkeologi, 1996)
Based on historical reviews, the speakers of Sundanese language are the descendants of Prince Achmad Djaketra and Prince Sugeri who used the title "Raden". BSJK speakers are now decreasing due to social factors, language geography and the position of their respective languages.